Influence of temperature on the growth of Dothiora sp. BIM Y-383 yeast culture and melanin synthesis - Gribanova, Ekaterina A.; Kurchenko, Vladimir P.; Azarko, Igor I.; Miamin, Vladislav E. (Experimental Biology and Biotechnology, 2026)
The effect of temperatures of 10; 18; 22; 28; 32 and 37 °C on the growth of Dothiora sp. BIM Y-383 yeast over 16 days of cultivation was studied. The yeast was shown to be psychrotolerant microorganisms with optimal culture growth and melanin synthesis at 22–28 °C. Melaninogenesis is most intense during the yeast culture death stage. Using spectral methods of analysis, it was established that on the 16th day of cultivation, the melanin content in extracts from freeze-dried yeast mycelium grown at temperatures of 10; 18; 22; 28 and 32 ℃ was (23.0 ± 0.5) mg/g, (39.0 ± 0.8) mg/g, (62.3 ± 1.2) mg/g, (69.0 ± 1.4) mg/g and (45.1 ± 0.9) mg/g, respectively.